Racial Disparities in Outcomes of Reconstructive Breast Surgery: An Analysis of 51,362 Patients from the ACS-NSQIP - Blankensteijn, Louise L.; Sparenberg, Sebastian; Crystal, Dustin T.; Ibrahim, Ahmed M.S.; Lee, Bernard T.; Lin, Samuel J. (Journal of Reconstructive Microsurgery, 2020)
Background In various surgical specialties, racial disparities in postoperative complications are widely reported. It is assumed that the effect of race can also be found in plastic surgical outcomes, although this remains largely undefined in literature. This study aims to provide data on the impact of race on outcomes of reconstructive breast surgery.Methods Data were collected using the NSQIP (National Surgical Quality Improvement Program) database (2008–2016). Outcomes of the reconstructive breast surgery of White patients were compared with those of African American, Asian, or other races. Logistic regression was performed to control for variations between all groups. Analysis of racial disparities was further sub-stratified according to four different types of breast reconstruction: delayed or immediate autologous, and delayed or immediate prosthesis-based reconstruction.Results In total, this study included 51,362 patients of which 43,864 were Caucasian, 5,135 African American, 2,057 Asian, and 332 of other races. When compared with White patients, patients of African American race had larger body mass indices (31.3 ± 7.0 vs. 27.6 ± 6.3, p-value < 0.001) in addition to higher rates of diabetes (12.3 vs 4.6%, p-value < 0.001) and hypertension (44.7 vs. 23.4%, p-value < 0.001). Both multivariate analysis and the sub-stratified analysis of different types of reconstruction showed no differences in overall complication rate.Conclusion Among the four types of reconstructive procedures, differences in surgical outcomes do not appear to be based on race and therefore seem to be less evident in reconstructive breast surgery compared with the current literature within other surgical specialties.
Keywords: reconstruction; breast reconstruction; race; minority; racial disparities; NSQIP